Pengaruh Penggunaan Media Audio Visual Dalam Mengembangkan Minat Belajar Siswa Di Sekolah - Harahap, Putri Husnul Khotimah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Learning media is one of the ways or tools used in the teaching and learning process. This is done to stimulate learning patterns so that they can support the success of the teaching and learning process so that teaching and learning activities can be effective in achieving the desired goals. There are so many kinds of learning media that can be utilized especially in this day and age the role of technology has entered various aspects, including the world of education. The function of learning media is to attract students' interest in the learning material presented. In addition to arousing student motivation and interest, instructional media can also help students improve understanding, present data in an interesting way and condense information. Educators can take advantage of technology that is currently developing rapidly, for example by using audio-visual learning media. Audio-visual media is media that has auditive (hearing) and visual (seeing) elements. The research method is descriptive quantitative, data collection uses a questionnaire, analysis of research data uses descriptive analysis. The results of the study show that audio-visual media is indeed very effective for learning in schools.